2000
DOI: 10.1034/j.1600-0420.2000.078004460.x
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy for regression of choroidal neovascularization with age‐related macular degeneration

Abstract: ABSTRACT.Objective: In age-related macular degeneration, the posterior vitreous surface often remains attached to a higher degree than expected for the patient's age, suggesting the involvement of the posterior vitreous membrane in the pathophysiology of choroidal neovascularization. Thus, we performed simple pars plana vitrectomy and artificial posterior vitreous detachment in order to induce regression of choroidal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
1
21
0
3
Order By: Relevance
“…The authors concluded that the persistent attachment of the posterior vitreous cortex to the macula may be a risk factor for developing exudative AMD, and that vitrectomy to create a PVD may have prophylactic benefits. Relevant to our case, a regression of a CNV in eyes with AMD has been described after vitrectomy to create a PVD 5. We found a firmly adherent vitreous cortex around the macula, which may have caused the development of a CNV after the cataract surgery in the fellow eye.…”
Section: Discussionsupporting
confidence: 77%
“…The authors concluded that the persistent attachment of the posterior vitreous cortex to the macula may be a risk factor for developing exudative AMD, and that vitrectomy to create a PVD may have prophylactic benefits. Relevant to our case, a regression of a CNV in eyes with AMD has been described after vitrectomy to create a PVD 5. We found a firmly adherent vitreous cortex around the macula, which may have caused the development of a CNV after the cataract surgery in the fellow eye.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, these tractional forces may antagonize the effects of anti-VEGF treatments and cause pharmacological resistance in those patients [29, 30]. Unfortunately, no published study has investigated whether there is an increase in vitreous VEGF levels in the presence of vitreoretinal interface pathologies or an alteration in the penetration of anti-VEGF drugs through the ERM in eyes with nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…23 It has also been shown that vitrectomy to detach the posterior vitreous cortex could improve CNV regression. 24 In 2 In contrast to other variable-dosing regime studies showing better outcomes, the presence of VMT often leads to poorer visual and anatomical outcomes during anti-VEGF therapy for wet AMD. Surgical intervention to address VMT is an option to be considered in managing this difficult group of patients when the expected response is not achieved.…”
Section: Discussionmentioning
confidence: 99%